2019
DOI: 10.12750/jarb.34.2.65
|View full text |Cite
|
Sign up to set email alerts
|

Current Strategies of Genomic Modification in Livestock and Applications in Poultry

Abstract: Birds have a distinguished history as a model system in the biosciences. Recent developments in genetic modification technologies, including the transposon-transposase and CRISPR/Cas9 systems, are expected to revolutionize genomic research when applied to avian species (Park et al., 2012; Park et al., 2019). Based on the methods of somatic cell nuclear transfer (SCNT) for animal cloning and direct injection into one-cell-stage embryo, numerous CRISPR/Cas9-mediated knockout and knock-in animals have been succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The knock-in of large DNA fragments has been restricted by technical difficulties attributed in part to the low efficiency of homologous recombination (HR) in cells. Recently, it was demonstrated that use of zinc finger nucleases (ZFN), transcription activator-like effector nucleases (TALEN), and the clustered regularly interspaced short palindromic repeats/ CRISPR-associated 9 (CRISPR/Cas9) system could enhance the knock-out or knock-in efficiency in mammalian cells compared to traditional methods [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The knock-in of large DNA fragments has been restricted by technical difficulties attributed in part to the low efficiency of homologous recombination (HR) in cells. Recently, it was demonstrated that use of zinc finger nucleases (ZFN), transcription activator-like effector nucleases (TALEN), and the clustered regularly interspaced short palindromic repeats/ CRISPR-associated 9 (CRISPR/Cas9) system could enhance the knock-out or knock-in efficiency in mammalian cells compared to traditional methods [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%